2002
DOI: 10.1002/jcp.10222
|View full text |Cite
|
Sign up to set email alerts
|

SNARE protein degradation upon platelet activation: Calpain cleaves SNAP‐23

Abstract: In order to better understand the molecular mechanisms of platelet granule secretion, we evaluated the effect of activation-induced degranulation on three functional platelet SNARE proteins, SNAP-23, VAMP-3, and syntaxin 4. Initial studies showed that SNAP-23 is lost upon SFLLRN-induced platelet activation. Experiments with permeabilized platelets demonstrated that proteolysis of SNAP-23 was Ca(2+)-dependent. Ca(2+)-dependent proteolysis of SNAP-23 was inhibited by the cell-permeable calpain inhibitors, calpep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 50 publications
0
18
0
1
Order By: Relevance
“…There are several reasons for this series of negative results, but the most likely explanation is that synaptobrevin/VAMP-2 is expressed at low levels and is degraded during sample preparation. Consistently, Lai and Flaumenhaft 29 have shown that cellubrevin/VAMP-3 can be degraded in activated platelets by an unknown protease, therefore degradation appears to be a key problem when examining platelet v-SNAREs. Taking this into consideration, we now demonstrate that synaptobrevin/ VAMP-2 is present in human platelets.…”
Section: Discussionmentioning
confidence: 74%
“…There are several reasons for this series of negative results, but the most likely explanation is that synaptobrevin/VAMP-2 is expressed at low levels and is degraded during sample preparation. Consistently, Lai and Flaumenhaft 29 have shown that cellubrevin/VAMP-3 can be degraded in activated platelets by an unknown protease, therefore degradation appears to be a key problem when examining platelet v-SNAREs. Taking this into consideration, we now demonstrate that synaptobrevin/ VAMP-2 is present in human platelets.…”
Section: Discussionmentioning
confidence: 74%
“…The degradation of SNAP-23 and phospho-SNAP-23 in A23187-stimulated platelets is consistent with reports that calpain cleaves SNAP-23 in highly activated platelets. 36,37 m-Calpain cleaves between Gly164 and Asn165 (supplemental Figure 1) but Ser95 phosphorylation does not affect cleavage. These data confirm that SNAP-23 is phosphorylated on Ser95 and show that SNAP-23 phosphorylation occurs in response to a range of agonists.…”
Section: Snap-23 Is Phosphorylated Upon Platelet Activation By Ikkmentioning
confidence: 98%
“…40 If platelets are permeabilized for 15 minutes or more in the absence of ATP, they will no longer secrete granules in response to Ca 2ϩ ( Figure 7). 41 Loss of responsiveness is secondary to diffusion of cytosolic ATP from the permeabilized platelet and can be reversed by addition of ATP to the incubation mixture ( Figure 7). If the resting cytoskeleton serves as a barrier to granule secretion, we reasoned that disruption of this barrier may substitute for ATP in priming platelets for granule secretion triggered by Ca 2ϩ or GTP-␥-S.…”
Section: Actin Cytoskeleton and Snare Protein-dependent Granule Secrementioning
confidence: 99%